ACCESS TO JUSTICE NASABAH PERBANKAN SYARIAH PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 93/PUU-X/2012 - Ro'fah Setyowati Dyah Wijaningsih Islamiyati Muhyidin (Faculty of Law, Universitas Diponegoro, 2014)
Dualism of absolute competence 'Access to justice ' Islamic banking consumers resulting in 'spiritual right' customers unprotected. This study aims to build a model of access to justice based on Islamic banking customer protection after the Constitutional Court Decision No. 93/PUU-X/2012. This study uses the doctrinal and non- doctrinal approach. The results of this study indicate there is non-compliance with the banking industry to the Constitutional Court Decision No. 93/PUU-X/2012, which establishes the authority of Islamic banking dispute resolution in the Religious Courts. It also shows yet protection of 'spiritual right' clients in dispute resolution